Synthesis and application of chromium complexes based on 4,5-bis(diphenylphosphanyl)-H-1,2,3-triazole ligands to obtain higher С10–С18 olefins - A. A. Senin; K. B. Polyanskii; A. M. Sheloumov; V. V. Afanasiev; T. M. Yumasheva; K. B. Rudyak; S. V. Vorobyev (Тонкие химические технологии, 2024)
Objectives. To synthesize 4,5-bis(diphenylphosphanyl)-H-1,2,3-triazole ligands and new chromium complexes based on them, in order to obtain a fraction of higher C10–C18 alpha-olefins from ethylene.Methods. The Schlenk technique was used to obtain the target chromium complexes. Diphenylphosphanyl triazole ligands can be characterized by nuclear magnetic resonance spectroscopy. The composition of the final products was confirmed by elemental analysis. The liquid phase of the oligomerization reaction was studied by gas chromatography.Results. L1–L9 ligands were obtained, and K1–K9 chromium complexes were synthesized based on the correspondent ligands using commercially available chromium (III) trichloride tris(tetrahydrofuran). The K1–K9 complexes thus obtained were tested in the process of ethylene oligomerization.Conclusions. Chromium complexes based on 4,5-bis(diphenylphosphanyl)-H-1,2,3-triazoles K1–K9 were produced in high yields using the Schlenk technique. It was found that systems based on the K4–K7 and K9 complexes enable the ethylene oligomerization process to be carried out with a sufficiently high level of productivity. It was shown that the introduction of a dialkyl zinc derivative increases the performance and selectivity of the catalytic system for the target fraction.